Synthesis and electrical properties of bismuth tantalate binary materials - Firman, Kartika (2018)
Phase-pure bismuth tantalate fluorites were successfully prepared via conventional solid-state method at 900 ˚C in 24 – 48 hours. The solid solution was proposed with the general formula of Bi3+xTa1-xO7-x (0 ≤ x ≤ 0.184), wherein the formation mechanism involved a one-to-one replacement of Ta5+cation by Bi3+cation within ~4.6 mol% difference. These samples crystallised in a cubic symmetry, space group Fm-3m with lattice constants, a=b=c in the range 5.4477(±0.0037) – 5.4580(±0.0039) Å. A slight increment in the unit cell was discernible with increasing Bi2O3 content and this may attribute to the incorporation of relatively larger Bi3+cation in the host structure. The linear correlation between lattice parameter and composition variable showed that the Vegard’s Law was obeyed. Both TGA and DTA analyses showed Bi3+xTa1-xO7-x samples to be thermally stable as neither phase transition nor weight loss was observed within ~28–1000 ˚C. The correct stoichiometry of sample was confirmed using inductively coupled-plasma optical emission spectroscopy (ICP-OES), in which a close agreement between experimental and theoretical values had been achieved. Electrical properties of Bi3+xTa1-xO7-x solid solution samples were measured over the frequency range 5 Hz – 13 MHz. At intermediate temperatures, ~350 – 850 ˚C, Bi3+xTa1-xO7-x solid solution was a modest oxide ion conductor with conductivity, ~10-6 – 10-3 S cm-1; the activation energy was in the range 0.98 – 1.08 eV. Bi-rich sample, Bi3.184Ta0.816O6.816 exhibited the highest conductivity of ~1.50x10-3 S cm-1 at 650 ˚C. The improved electrical conductivity could be a result of the structural change in terms of the grain size, surface morphology and oxygen vacancies with increasing bismuth content. Solid solutions with general formula of Bi3Ta1-xLnxO7-x (Ln = Nd, Gd and La) had been successfully prepared. The formation mechanism involved a proportion amount of Ta5+ cation replaced by Ln3+ cation with creation of oxygen vacancy for charge compensation. Therefore, the overall charge electroneutrality of the system was preserved through a mechanism: Ln3+ ↔ Ta5+ + O2. The solid solution limit was up to x = 0.2 for Nd-doped Bi3Ta1-xNdxO7-x, with a slight increased lattice constants, a=b=c in the range 5.4477(±0.0037) – 5.4682(±0.0009) Å. The increment of unit cell may attribute to the larger Nd3+ ionic radius of 0.983 Å if compare to Ta5+ of 0.64 Å at 6-fold coordination. Meanwhile, only limited solid solution range, i.e. x = 0.1 for both Gd- and Laseries. The recorded lattice constants, a=b=c were 5.4635(±0.0002) and 5.4687(±0.0002) Å, respectively. Bi3Ta0.8Nd0.2O6.8 exhibited the highest conductivity for the doped lanthanide series at all temperatures, i.e. ~350 to 850 ˚C. The recorded conductivity was 9.26x10-3 S cm-1 at 650 C. A selection of pentavalent cations was introduced at either Bi-site or Ta-site of Bi3TaO7. However, only substitution of Ta-site was able to yield new solid solution using Nb5+ and V5+, respectively. The solid solution mechanism is proposed to be a one-to-one replacement of Ta by Nb or V, with the general formula of Bi3Ta1-xMxO7 (M = V or Nb). The solid solution limit for Nb–doped Bi3Ta1-xNbxO7 was up to x = 0.5. Bi3Ta1-xNbxO7solid solution adopted similar defective fluorite structure, space group Fm-3m with lattice parameters, a=b=c in the range 5.4477(±0.0037) – 5.4654(±0.0011) Å.The Nb-doped samples showed an increase in electrical conductivity with increasing Nb content; Bi3Ta0.5Nb0.5O7 exhibited the highest conductivity, ~5.96x10-3 S cm-1 at 650 ˚C. The enhanced electrical conductivity for Bi3Ta1-xNbxO7solid solution may attribute to the large and well-connected grains that could reduce the impedance barrier for the charge transfer in samples. On the other hand, a limited solid solution range of x = 0.1 was attainable for Bi3Ta1-xVxO7solid solution with lattice parameters, a=b=c, 5.4559 ((±0.0011) Å. The ionic conductivity exhibited by Bi3Ta0.9V0.1O7 was ~4.17x10-3 S cm-1 at 650 ˚C with activation energy of 1.01 eV. On the other hand, tungsten substituted solid solution, Bi3Ta1-xWxO7+(x/2) (0 ≤ x ≤ 0.2) with lattice constants, a=b=c in the range 5.4477(±0.0037) – 5.4668(±0.0001) Å. The conductivity values of Bi3Ta1-xWxO7+(x/2) solid solution, x = 0.1 and x = 0.2 were ~5.15x10-3 S cm-1 and ~6.78x10-3 S cm-1at 650 C, respectively. These conductivity values appeared to be comparable to other doped series, e.g. Nb, V, and slightly higher than that of the parent phase. The relatively higher conductivity of tungsten doped samples may somewhat correlate to minor contribution of electronic conductivity that resulted from the variable oxidation state of tungsten. In conclusion, Bi3TaO7 and related materials were successfully synthesised by solid-state reaction at the optimised conditions. These materials exhibited interesting oxide ionic conductivity that may attribute to the high concentration of oxygen vacancy in the host lattice. The structural and electrical properties of Bi3TaO7 and related materials had been demonstrated to be highly dependent on the composition and crystal structure.